Comunicação pública e divulgação científica em parques tecnológicos credenciados pelo Sistema Paulista de Parques Tecnológicos - Arruda, Adriana Gonçalves (2017)
The study characterized the area of communication and the scientific popularization in science park environments, which aims to strengthen science, technology and innovation through the realization of partnerships and, thus, boost the socioeconomic development of a country. The study assumes that, although the science parks are projects that reach the most diverse agents and receive public funding, they have an unidirectional public communication, which is not very accessible to the citizen. In this sense, this research maps the strategies and tools of scientific outreach used by science park environments and analyzes journalistic products published by science parks. It also verifies if they approach the STS Studies – which explores the importance of the democratization of knowledge from the relations between these three agents: science, technology and society – and the democratic model of public communication according to the criteria already established in the field literature. This qualitative exploratory research used mixed data collection procedures and considered the communication of four science parks that have definitive accreditation by the São Paulo System of Science Parks – Science Parks of Ribeirão Preto, Santos, São Carlos and São José dos Campos. This study starts with the presentation of some bibliographical studies, which will help to understand the importance of public communication and scientific outreach in the area of science, technology and innovation and will show the historical and current contexts of technological parks in Brazil, more specifically in the State of São Paulo. It proceeds with a field study with interviews with press officers, outsourced agents and managers of science parks. Finally, analyzes are presented – from interviews and journalistic products – to evaluate whether the communication area of these parks make public communication and whether they are similar to the preestablished criteria of communication in STS Studies. The results found herein contribute to studies in public communication of science, scientific outreach in innovation environments and public perception of science and technology.